2000
DOI: 10.1021/np000012y
|View full text |Cite
|
Sign up to set email alerts
|

New Quinoline Alkaloids from Ruta chalepensis

Abstract: The roots of Ruta chalepensis, collected from the northern Saudi desert, yielded two new quinoline alkaloids, namely, 2-¿6'-(2H-benzo[d]1' ',3' '-dioxolen-5' '-yl)hexyl¿-hydroquinolin-4-one (1) and 2-¿6'-(2H-benzo[d]1' ',3' '-dioxolen-5' '-yl)hexyl¿-4-methoxy-quinoline (2). Nine previously reported alkaloids, dictamnine, pteleine, skimmianine, rutacridone, isogravacridonechlorine, maculosidine, graveoline, graveolinine, and 4-methoxy-1-methyl-2(1H)-quinolinone, and coumarins, chalepensin, and umbelliferone wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
37
0
3

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(43 citation statements)
references
References 10 publications
3
37
0
3
Order By: Relevance
“…Pharmacological studies carried out with different extracts of Ruta species reported the antiinfl ammatory properties (Atta and Al-Kofahi, 1998), antipyretic (Al-Said et al 1990), antifertility activity (Ulubelen et al 1994), antifungal (Ali-Shtayeh et al 1999) and antibacterial effect (El Sayed et al 2000). Contact dermatitis and photoxicity characterized by erythema, itching and burning of the skin is a common toxic effect, which is usually associated with all Ruta species (Gijon et al 1995;Heskel et al 1983).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pharmacological studies carried out with different extracts of Ruta species reported the antiinfl ammatory properties (Atta and Al-Kofahi, 1998), antipyretic (Al-Said et al 1990), antifertility activity (Ulubelen et al 1994), antifungal (Ali-Shtayeh et al 1999) and antibacterial effect (El Sayed et al 2000). Contact dermatitis and photoxicity characterized by erythema, itching and burning of the skin is a common toxic effect, which is usually associated with all Ruta species (Gijon et al 1995;Heskel et al 1983).…”
Section: Introductionmentioning
confidence: 99%
“…Phytochemical investigations of R. chalepensis reported isolation of furanocoumarins, acridone and quinoline alkaloids, terpenoids, saponins and tannins (El Sayed et al 2000;El Tawil et al 1980;Gray and Watermann, 1978;Husain and Devy, 1998;Ulubelen et al 1988). However, published literature did not report anti-platelet activity of R. chalepensis herb or its constituents.…”
Section: Introductionmentioning
confidence: 99%
“…Analysis of the 1 H-and 13 C-NMR spectra, including HSQC, coupled with biogenetic considerations, suggested the presence of a C 10 terpenoid side chain with two trisubstituted oxirane rings in the molecule. The 1 H-NMR chemical shifts of the 3-H singlet (MeÀC(3')) and the CH double doublet (HÀC(2')) coupled with 13 Cchemical shifts of C(2') and a fully substituted C-atom C(3'), and the 1 H-chemical shifts of two 3 H-singlets (Me 2 ÀC(7')) and the CH double doublet (HÀC(6')) coupled with 13 C-chemical shifts of C(6') and a fully substituted C-atom C(7') suggested the presence of two trisubstituted oxirane rings, respectively. The connectivity of these signals was elucidated by HMBCs of HÀC(2') with C(3') and MeÀC(3'), of HÀC(6') with Me a ÀC(7'), Me b ÀC(7'), and C(7').…”
mentioning
confidence: 99%
“…The findings of this study are in agreement with previous reports on the antifungal activity of Echinops sp., Ruta chalepensis, Thymus serrulatus and Artemisia genus [13,14,16,23]. Previous phytochemical investigation of Ruta chalepensis resulted in isolation of a number of alkaloids and coumarins and the active ingredients of this plant have antifungal properties that could prove beneficial to agriculture [12,24].…”
Section: Discussionmentioning
confidence: 99%
“…There is a need for continued research efforts to developing effective and economical alternative methods for the management of papaya anthracnose. Most plant specious used in this experiment had medicinal value and are known to contain a number of secondary substances with antimicrobial properties and are toxic to phytopathogens [6,[12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%